2015
DOI: 10.3937/kampomed.66.327
|View full text |Cite
|
Sign up to set email alerts
|

<b>Hangebyakujutsutenmato can Decrease the Adverse Effects of Opioids in Chronic Pain Patients : Two Case Reports</b>

Abstract: We report on two cases of patients with chronic pain treated with opioid analgesics. They did not continue their treatment with opioid because of side effects. An 88 year-old female complained of low back and leg pain caused by lumbar spinal canal stenosis. She also complained of dizziness, nausea and appetite loss after a course of weak oral opioid was administered. We thought it necessary to improve her general condition and digestive sickness following treatment for pain, and administered 5 g/day of hangeby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Regarding its potential as a therapy for PPPD, HBT has been reported as a potential treatment for CSD[ 13 , 16 , 17 ]. In addition, some reports indicated that HBT was effective in preventing dizziness caused by opioids[ 18 ] or pregabalin[ 19 ]. Thus, HBT is a promising drug based on its demonstrated effects on dizziness.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its potential as a therapy for PPPD, HBT has been reported as a potential treatment for CSD[ 13 , 16 , 17 ]. In addition, some reports indicated that HBT was effective in preventing dizziness caused by opioids[ 18 ] or pregabalin[ 19 ]. Thus, HBT is a promising drug based on its demonstrated effects on dizziness.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese kampo medicine hangebyakujutsutemmato (HBT), however, also known as ‘banxiabaizhutianmatang’ in Chinese traditional herbal medicine, has been used to prevent dizziness and nausea . Recently, Hamaguchi et al reported that HBT was effective in preventing dizziness caused by opioids . Furthermore, Onaka et al reported that HBT was effective in treating dizziness resulting from neuropathic pain treatments, including pregabalin .…”
Section: Introductionmentioning
confidence: 99%